Upward influence strategies: relationship with academics' career advancement - Mat Zin, Sakinah; Ngah, Nazlin Emieza; Ismail, Rusnah; Ibrahim, Norlaila; Jusoff, Kamaruzaman; Salleh, Asri; Ahmad Tajuddin, Nur Hafizah (IDOSI Publications, 2011)
Often times, in academia world, academics report to superiors who are not from similar backgrounds and do not share the same standards, points of view or needs. Hence, to be effective, any particular academic staff must understand that upward power is partly based on the ability and willingness to use influence tactics. The aim of this paper is to provide an in-depth analysis of the relationship between upward influence strategies and employees’ career success. All three dimensions of upward influence strategies i.e. soft, hard and rational tactics have different effects towards career progression due to the nature of the tactics. The paper argues that career advancement, assuming that all other factors are equal, is a very subjective matter which lies upon three main influencing factors of ingratiation, assertiveness and reasoning.